Foreword: The Rocky Road Toward the Rule of Law in China: 1979-2000 - Friend, James Hugo (2000)
This Twentieth Anniversary Issue of JILB again has a symposium on law in China entitled China Revisited: Examining the Rule of Law After Twenty Years. The impetus for the 2000 China Symposium is the unprecedented integration of China into the world economic community, evidenced by China's imminent entry into the World Trade Organization ( WTO ).2 The road to China's integration into the WTO was paved by the U. S. Senate's recent vote, the most significant advance in U.S.-China relations since President Nixon's 1972 visit,'13 which grants China permanent normalized trade relations without annual Congressional review. Although the Senate approval was expected, the overwhelming margin of 83 to 15 was not, highlighting the fact that a strong majority of legislators and Americans support normal and mutually productive commercial relations with the PRC. With China still at the forefront of vital issues relating to international law and commerce, no topic is more pressing and appropriate to mark JILB's twenty years of publication than a second symposium addressing the evolution of the rule of law in China and its impact on commercial transactions with China